A method for preparing CsPbIBr2 perovskite solar cells using precursor liquid engineering

By adjusting the ratio and concentration of the precursor liquid of CsPbIBr2 perovskite solar cell, the problem of insufficient perovskite film thickness in the prior art is solved, and a more efficient photoelectric conversion efficiency is achieved.

CN115954400BActive Publication Date: 2025-04-04DALIAN UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310152709.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-22
Publication Date
2025-04-04
Estimated Expiration
2043-02-22

AI Technical Summary

Technical Problem

The precursor liquid of the existing CsPbIBr2 perovskite solar cell has a low solubility, resulting in insufficient thickness of the prepared perovskite film and cannot meet the optimal thickness requirements of high-efficiency inorganic perovskite solar cells.

Method used

The raw materials and ratio of the perovskite precursor liquid were adjusted, and the molar ratio of the three-component precursor (CsBr:PbI2:PbBr2=2:1:1) was used to introduce lead iodide and adjust the concentration to 1.4M to prepare a perovskite film with higher light absorption capacity.

Benefits of technology

By increasing the concentration of the precursor liquid and adjusting the ratio, a perovskite film with increased thickness and improved quality was successfully prepared, which improved the photoelectric efficiency of perovskite solar cells and increased the efficiency by more than 16%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115954400B_ABST
    Figure CN115954400B_ABST
Patent Text Reader

Abstract

A kind of precursor liquid engineering preparation of CsPbIBr 2 A method for preparing a perovskite solar cell belongs to the technical field of preparing a perovskite solar cell. The method includes: pretreatment of a substrate, preparation of an electron transport layer, a perovskite film, a hole transport layer and an electrode. The method increases the concentration of the precursor solution by adjusting the raw materials and ratio of the precursor solution, thereby increasing the thickness of the perovskite film and enhancing its light absorption capacity. The method converts CsPbIBr 2 The efficiency of perovskite solar cells has increased by 16%. The perovskite film obtained by this method has larger grains and fewer grain boundaries, which can effectively reduce the non-radiative recombination losses of the cell and obtain a stable and efficient perovskite solar cell.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of perovskite solar cells and provides a method for preparing a CsPbIBr2 perovskite solar cell by precursor liquid engineering. Background Art

[0002] Perovskite solar cells have developed rapidly. Since their birth in 2009, their efficiency has rapidly jumped from 3.8% to 25.7%, showing great application prospects. So far, all the most efficient cells use organic-inorganic hybrid perovskites, but organic perovskites are particularly easy to decompose under conditions of high heat and high humidity. + Completely replacing the organic components to form all-inorganic perovskites is an effective way to solve this problem [1] Among all-inorganic perovskites, CsPbIBr2 perovskite has both a suitable band gap (2.09 eV) and environmental phase stability, making it an ideal choice for preparing stable and efficient polycrystalline materials. However, CsPbIBr2 perovskite solar cells still face many challenges. In order for the perovskite to fully absorb the incident light, the optimal film thickness should be at least 400 nm in principle. [2] However, the current CsPbIBr2 perovskite precursor solution only relies on equimolar CsI and PbBr2, and the solubility of Br salt is low, resulting in a low molar concentration of the precursor solution; and the thickness of the film prepared by this method is usually about 260-280nm, which is far lower than the optimal value (400-600nm) required for high-efficiency inorganic perovskite solar cells.

[0003] [1]Wang H, Li H, Cao S, et al. Interface Modulator of Ultrathin MagnesiumOxide for Low-Temperature-Processed Inorganic CsPbIBr2 Perovskite Solar Cells with Efficiency Over 11% [J]. Solar RRL, 2020, 4.

[0004] [2]Jiang Y, Yuan J, Ni Y, et al. Reduced-Dimensionalα-CsPbX3 Perovskites for Efficient and Stable Photovoltaics[J]. Joule, 2018, 2. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a method for preparing CsPbIBr2 perovskite solar cells by precursor engineering. The present invention overcomes the solubility problem of the CsPbIBr2 precursor solution, thereby preparing a thicker perovskite film with sufficient light absorption, improving the quality of the perovskite film, and increasing the efficiency of the perovskite solar cell.

[0006] In the prior art, the formula of CsPbIBr2 precursor solution is 1 mmol of PbBr2 and 1 mmol of CsI dissolved in 1 mL of DMSO, and the concentration of the obtained precursor solution is 1 M (measured in terms of cesium ion concentration, abbreviated as DCP, Double Component Precursor).

[0007] In order to solve the problems existing in the prior art, the technical solution adopted by the present invention is:

[0008] Adjust the raw materials and ratio of the perovskite precursor solution to produce a thicker perovskite film with sufficient light absorption; at the same time, adjust the crystallization process to obtain a high-quality perovskite film with larger grains and fewer grain boundaries. In this application, lead iodide is introduced to replace part of the lead salt in DCP, and cesium salt is subsequently used to supplement the bromine required for stoichiometry. A three-component precursor with a molar ratio of CsBr:PbI2:PbBr2=2:1:1 is used to prepare the CsPbIBr2 perovskite precursor solution. By changing the concentration of the precursor, the formula can obtain a maximum concentration of 1.4M for the precursor solution to overcome the solubility problem of the CsPbIBr2 precursor solution (for simplicity, it will be referred to as (TCP, Three Component Precursor)).

[0009] A method for preparing CsPbIBr2 perovskite solar cells by precursor liquid engineering, comprising the following steps:

[0010] (1) Pretreatment of the substrate: ultrasonically clean the substrate using detergent, deionized water, acetone, and ethanol; after cleaning, blow dry, and treat with ultraviolet light;

[0011] (2) Preparation of electron transport layer: depositing an electron transport material solution on a substrate by thermal spraying and sintering in a flat furnace to obtain an electron transport layer;

[0012] (3) Preparation of precursor solution:

[0013] The perovskite precursor solution uses three components: cesium bromide, lead iodide and lead bromide. The concentration c of the perovskite precursor solution is calculated based on the concentration of cesium ions, 1M<c≤1.4M; the molar ratio of cesium bromide: lead iodide: lead bromide is 2:1:1; the molar ratio of lead iodide: lead bromide = 1:1 is first dissolved in dimethyl sulfoxide, and stirred at 50-70°C overnight; cesium bromide is added in molar ratio, and stirred until completely dissolved to obtain a perovskite precursor solution; the hole transport layer precursor solution uses 2,2',7,7'- Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene and a mixed additive are prepared in a ratio of 0.9-1g:1L, wherein the volume ratio of bis(trifluoromethane)sulfonyl imide:tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridinium]cobalt tris(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide salt):4-tert-butylpyridine in the mixed additive is 1:(1.6-2):(1.5-1.9);

[0014] (4) Preparation of perovskite film: preheat the substrate on a hot plate at 50-80°C, then spin-coat the perovskite precursor solution on the substrate, and anneal on a hot plate at 200-250°C for 5-15 minutes to obtain a perovskite film;

[0015] (5) Preparation of hole transport layer: drop the hole transport layer precursor on the perovskite film and spin coat at 2000-3000 rpm for 30-50 seconds;

[0016] (6) Preparation of electrodes: A layer of gold or silver is deposited on the hole transport layer by vacuum evaporation as an electrode.

[0017] The perovskite precursor solution and the hole transport layer precursor solution were filtered with a 0.22 μm filter head before use.

[0018] The spin coating process of the perovskite precursor solution uses 1000-2000 rpm for 10-20 seconds in the first stage and 3000-4000 rpm for 20-40 seconds in the second stage.

[0019] The electron transport layer is a tin oxide or titanium oxide layer;

[0020] When the electron transport layer is a titanium oxide layer, a titanium oxide solution is sprayed on the FTO substrate by a pyrolysis spray method;

[0021] When the electron transport layer is a tin oxide layer, a chemical bath deposition method is used to deposit the tin oxide layer on the FTO substrate.

[0022] Further, the following technical solutions can be adopted:

[0023] The pretreatment of the substrate in step (1) includes: ultrasonically cleaning the FTO substrate for 30 minutes using detergent, deionized water, acetone, and ethanol, respectively. After cleaning, the substrate is dried using a hair dryer, and then treated with ultraviolet light for 30 minutes.

[0024] The preparation material of the electron transport layer in step (2) includes one of SnO2 and TiO2.

[0025] When the electron transport layer is TiO2, the titanium oxide solution is sprayed on the FTO substrate by a pyrolysis spray method; wherein the volume ratio of bis(2,4-pentanedione)bis(2-propanoate)titanium and ethanol in the electron transport material solution is 1:9;

[0026] When the electron transport layer is SnO2, the FTO substrate is deposited in a tin oxide aqueous solution for 4 hours by chemical bath deposition. The electron transport material solution contains 137.5 mg of stannous chloride dihydrate, 12.5 μL of thioglycolic acid, 625 mg of hydrochloric acid, 625 μL of urea, and 50 mL of deionized water.

[0027] Step (3) The preparation of the precursor solution includes

[0028] The three-component (TCP) perovskite precursor solution uses a molar ratio of cesium bromide: lead iodide: lead bromide (CsBr:PbI2:PbBr2) dissolved in 1mL of dimethyl sulfoxide (DMSO). The specific method is to dissolve the molar ratio of lead iodide: lead bromide = 1:1 in 1mL of dimethyl sulfoxide (DMSO), stir at 60℃ overnight; add cesium bromide in a molar ratio 1h before use, stir until completely dissolved before use. By dissolving different concentrations of precursors, the perovskite precursor concentration can be obtained to be 1.0-1.4mol / L.

[0029] The hole transport layer precursor solution was prepared by combining 72.3 mg of Spiro-OMeTAD and additives (17.5 μL Li-TFSI, 30 μL FK209Co(III)TFSI and 28.8 μL t-BP).

[0030] The perovskite precursor solution and the hole transport layer precursor solution were filtered with a 0.22 μm filter head before use.

[0031] The preparation method of step (4) is to first preheat the substrate on a hot plate at 60°C for 5 minutes, then spin-coat the perovskite precursor solution on the substrate, using 1500 rpm for 15 seconds in the first stage and 3500 rpm for 30 seconds in the second stage, and anneal on a hot plate at 225°C for 10 minutes.

[0032] The preparation method of step (5) is to drop the hole precursor liquid on the perovskite film, then spin-coat it at 3000 rpm for 30 seconds, and finally anneal it at 60° C. for 10 minutes.

[0033] The electrode material in step (6) is one of gold and silver.

[0034] The photoelectric efficiency of the CsPbIBr2 perovskite solar cell prepared by the above method is 11.03%.

[0035] The beneficial effects of the present invention are:

[0036] Adjust the raw materials and ratio of the perovskite precursor solution to obtain a higher concentration of precursor solution. Thus, a thicker perovskite film with sufficient light absorption is obtained, which increases the light capture efficiency. In addition, the crystallization process of perovskite is adjusted, the quality of the perovskite film is improved, and the charge extraction and transfer are strengthened. Compared with DCP, the efficiency of TCP-based perovskite solar cells has been significantly improved by more than 16%. The process of adjusting the precursor solution to prepare high-efficiency perovskite solar cells is simple and convenient to prepare, providing a feasible strategy for the development of perovskite solar cells and a path for the commercialization of perovskite solar cells. TCP 1.2M precursor solution obtains a higher quality perovskite film with larger film grains and fewer grain boundaries, which can effectively reduce the non-radiative recombination loss of the battery and obtain a stable and efficient perovskite solar cell. However, when TCP 1.4M, although the grains of the perovskite film are significantly enlarged, the crystallization strength is weak and the surface roughness increases, which reduces the efficiency of the solar cell and has an adverse effect on the perovskite solar cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 These are physical pictures of perovskite precursor solutions; a) is a two-component perovskite precursor solution, and b) is a three-component perovskite precursor solution of different concentrations (1M, 1.2M, 1.3M and 1.4M).

[0038] Figure 2 Cross-sectional SEM of the all-inorganic CsPbIBr2 perovskite films of Example 1 and Comparative Examples 1-2, where a), b), and c) correspond to DCP, TCP 1.2M, and TCP 1.4M, respectively, and the corresponding thicknesses are 280nm, 370nm, and 420nm, respectively.

[0039] Figure 3 UV-vis of the all-inorganic CsPbIBr2 perovskite films of Example 1 and Comparative Examples 1-2. Figure 4 Planar SEM of the all-inorganic CsPbIBr2 perovskite films of Example 1 and Comparative Examples 1-2, a), b), and c) correspond to DCP, TCP 1.2M, and TCP 1.4M, respectively.

[0040] Figure 5 XRD of the all-inorganic CsPbIBr2 perovskite film in Example 1 and Comparative Examples 1-2.

[0041] Figure 6 J-V curves of the all-inorganic CsPbIBr2 perovskite cells in Example 1 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0042] Example 1

[0043] (1) Pretreatment of the substrate: The substrate was ultrasonically cleaned for 30 minutes using detergent, deionized water, acetone, and ethanol, respectively. After cleaning, the substrate was blown dry with a hair dryer and then treated with ultraviolet ozone for 30 minutes.

[0044] (2) Preparation of electron transport layer: Titanium (IV) bis(2,4-pentanedione) bis(2-propanoate) and ethanol were mixed in a volume ratio of 1:9, filtered and poured into a spray pot, and evenly sprayed on the FTO substrate by thermal spraying, and then sintered in a flat furnace at 500°C for 30 minutes to obtain a compact titanium oxide layer.

[0045] (3) Preparation of precursor solution:

[0046] Three-component (TCP) perovskite precursor solution: 0.6 mmol lead iodide and 0.6 mmol lead bromide were first dissolved in 1 mL dimethyl sulfoxide (DMSO) and stirred at 60°C overnight; 1.2 mmol cesium bromide was added in molar ratio 1 h before use and stirred until completely dissolved before use. It is marked as TCP 1.2M.

[0047] The hole transport layer precursor solution was prepared by combining 72.3 mg of Spiro-OMeTAD and additives (17.5 μL Li-TFSI, 30 μL FK209Co(III)TFSI and 28.8 μL t-BP).

[0048] (4) Preparation of perovskite film: First, the substrate was preheated on a hot plate at 60°C for 5 min, and then the perovskite precursor solution was spin-coated on the substrate at 1500 rpm for 15 s in the first stage and at 3500 rpm for 30 s in the second stage, followed by annealing on a hot plate at 225°C for 10 min.

[0049] (5) Preparation of hole transport layer: The prepared precursor solution was dropped onto the perovskite and then spin coated at 3000 rpm for 30 seconds.

[0050] (6) Preparation of electrode: A layer of silver was deposited on the hole transport layer by vacuum evaporation method with a thickness of 100 nm as the electrode.

[0051] Example 2

[0052] (1) Pretreatment of the substrate: The substrate was ultrasonically cleaned for 30 minutes using detergent, deionized water, acetone, and ethanol, respectively. After cleaning, the substrate was blown dry with a hair dryer and then treated with ultraviolet ozone for 30 minutes.

[0053] (2) Preparation of electron transport layer: Titanium (IV) bis(2,4-pentanedione) bis(2-propanoate) and ethanol were mixed in a volume ratio of 1:9, filtered and poured into a spray pot, and evenly sprayed on the FTO substrate by thermal spraying, and then sintered in a flat furnace at 500°C for 30 minutes to obtain a compact titanium oxide layer.

[0054] (3) Preparation of precursor solution:

[0055] Three-component (TCP) perovskite precursor solution: 0.7 mmol lead iodide and 0.7 mmol lead bromide were first dissolved in 1 mL dimethyl sulfoxide (DMSO) and stirred at 60°C overnight; 1.4 mmol cesium bromide was added in molar ratio 1 h before use and stirred until completely dissolved before use. It is marked as TCP 1.4M.

[0056] The hole transport layer precursor solution was prepared by combining 72.3 mg of Spiro-OMeTAD and additives (17.5 μL Li-TFSI, 30 μL FK209Co(III)TFSI and 28.8 μL t-BP).

[0057] (4) Preparation of perovskite film: First, the substrate was preheated on a hot plate at 60°C for 5 min, and then the perovskite precursor solution was spin-coated on the substrate at 1500 rpm for 15 s in the first stage and at 3500 rpm for 30 s in the second stage, followed by annealing on a hot plate at 225°C for 10 min.

[0058] (5) Preparation of hole transport layer: The prepared precursor solution was dropped onto the perovskite and then spin coated at 3000 rpm for 30 seconds.

[0059] (6) Preparation of electrode: A layer of silver was deposited on the hole transport layer by vacuum evaporation method with a thickness of 100 nm as the electrode.

[0060] Comparative Example 1

[0061] (1) Pretreatment of the substrate: The substrate was ultrasonically cleaned for 30 minutes using detergent, deionized water, acetone, and ethanol, respectively. After cleaning, the substrate was blown dry with a hair dryer and then treated with ultraviolet ozone for 30 minutes.

[0062] (2) Preparation of electron transport layer: Titanium (IV) bis(2,4-pentanedione) bis(2-propanoate) and ethanol were mixed in a volume ratio of 1:9, filtered and poured into a spray pot, and evenly sprayed on the FTO substrate by thermal spraying, and then sintered in a flat furnace at 500°C for 30 minutes to obtain a compact titanium oxide layer.

[0063] (3) Preparation of precursor solution:

[0064] The two-component (DCP) perovskite precursor solution uses 367mg of lead bromide (PbBr2) and 259mg of cesium iodide (CsI) dissolved in 1mL of dimethyl sulfoxide (DMSO). The specific method is to first dissolve 367mg of lead bromide (PbBr2) in 1mL of dimethyl sulfoxide (DMSO) and stir overnight at 60°C; add 259mg of cesium iodide (CsI) 1h before use and stir until completely dissolved before use. The hole transport layer precursor solution is prepared by combining 72.3mg of Spiro-OMeTAD and additives (17.5μLLi-TFSI, 30μL FK209Co(III)TFSI and 28.8μL t-BP).

[0065] (4) Preparation of perovskite film: First, the substrate was preheated on a hot plate at 60°C for 5 min, and then the perovskite precursor solution was spin-coated on the substrate at 1500 rpm for 15 s in the first stage and at 3500 rpm for 30 s in the second stage, followed by annealing on a hot plate at 225°C for 10 min.

[0066] (5) Preparation of hole transport layer: The prepared precursor solution was dropped onto the perovskite and then spin coated at 3000 rpm for 30 seconds.

[0067] (6) Preparation of electrode: A layer of silver was deposited on the hole transport layer by vacuum evaporation method, with a thickness of 100 nm.

[0068] Comparative Example 2

[0069] (1) Pretreatment of the substrate: The substrate was ultrasonically cleaned for 30 minutes using detergent, deionized water, acetone, and ethanol, respectively. After cleaning, the substrate was blown dry with a hair dryer and then treated with ultraviolet ozone for 30 minutes.

[0070] (2) Preparation of electron transport layer: Titanium (IV) bis(2,4-pentanedione) bis(2-propanoate) and ethanol were mixed in a volume ratio of 1:9, filtered and poured into a spray pot, and evenly sprayed on the FTO substrate by thermal spraying, and then sintered in a flat furnace at 500°C for 30 minutes to obtain a compact titanium oxide layer.

[0071] (3) Preparation of precursor solution:

[0072] Three-component (TCP) perovskite precursor solution: 0.5mmol lead iodide and 0.5mmol lead bromide were first dissolved in 1mL dimethyl sulfoxide (DMSO) and stirred at 60℃ overnight; 1mmol cesium bromide was added in molar ratio 1h before use and stirred until completely dissolved before use. It is marked as TCP 1.0M.

[0073] The hole transport layer precursor solution was prepared by combining 72.3 mg of Spiro-OMeTAD and additives (17.5 μL Li-TFSI, 30 μL FK209Co(III)TFSI and 28.8 μL t-BP).

[0074] (4) Preparation of perovskite film: First, the substrate was preheated on a hot plate at 60°C for 5 min, and then the perovskite precursor solution was spin-coated on the substrate at 1500 rpm for 15 s in the first stage and at 3500 rpm for 30 s in the second stage, followed by annealing on a hot plate at 225°C for 10 min.

[0075] (5) Preparation of hole transport layer: The prepared precursor solution was dropped onto the perovskite and then spin coated at 3000 rpm for 30 seconds.

[0076] (6) Preparation of electrode: A layer of silver was deposited on the hole transport layer by vacuum evaporation method with a thickness of 100 nm as the electrode.

[0077] Figure 1 The concentration limits of precursor solutions obtained by different DCP and TCP are shown; the maximum concentration of precursor solution obtained by TCP is 1.4 M. Figure 1 In b), it can be seen that the precursor solution has become slightly turbid when the concentration reaches 1.4M. The thickness of the CsPbIBr2 perovskite film was analyzed by cross-sectional SEM. Figure 2 As shown, the thickness of the perovskite in Example 1 is about 370 nm, and the thickness of the perovskite in Comparative Example 1 and Comparative Example 2 are about 280 and 420 nm, respectively, which is due to the increase in the concentration of the precursor solution. Figure 3 The UV-vis spectra in Figure 4 verify that thicker perovskite films are conducive to more complete light absorption. The absorption intensity increases significantly with the increase of precursor solution concentration.

[0078] The use of a three-component perovskite precursor solution not only obtains a film that can absorb more visible light, but also regulates the crystallization process of the perovskite film, thereby obtaining a high-quality perovskite film. Figure 4 As shown, it can be clearly seen that Figure 4 a) The surface of DCP 1.0M film is rough and the grain boundaries are obvious, which easily leads to defects. Figure 4b) The precursor solution is TCP1.2M. The increase in concentration significantly improves the film morphology, with a dense surface and uniform grain size. The perovskite film composed of larger grains has fewer grain boundaries, which will significantly reduce the recombination of carriers and thus improve device performance. It is worth noting that when the concentration increases to 1.4M Figure 4 In (c), the grain size increases significantly, even exceeding 1 μm, but this also leads to an increase in the surface roughness of the film, which will have an adverse effect on the interface conduction. The phase purity of the perovskite film was determined by XRD spectra ( Figure 5 ), there are three strong diffraction peaks at 15.2°, 21.5° and 30.4°, corresponding to the (10 0), (11 0) and (2 0 0) characteristic crystal planes of cubic CsPbIBr2 perovskite, respectively. It is worth noting that when TCP is 1.2M in Example 1, the peak intensity increases, which is due to the supersaturation of the precursor solution promoting the crystallization of the perovskite. However, when the concentration of the precursor solution is further increased to 1.4M (Example 2), we can see that the crystallization intensity decreases. The possible reason is that the TCP 1.4M precursor clusters are larger, resulting in fewer nucleation sites, and the rapid evaporation of the solvent during annealing will inevitably lead to a rough film. It is worth noting that the TCP 1.2M grains are already large enough and the absorption thickness is also large enough.

[0079] Table 1 Device efficiency of all-inorganic CsPbIBr2 perovskite solar cells

[0080]

[0081]

[0082] It can be seen from Examples 1, 2 and Comparative Example 2 that the concentration is the key factor in determining the efficiency under the same conditions of the components in the precursor solution. The raw materials and ratio of the perovskite precursor solution are adjusted to obtain a higher concentration of the precursor solution; thereby obtaining a thicker perovskite film with sufficient light absorption, thereby increasing the light capture efficiency. The above-mentioned effects increase the efficiency of the all-inorganic CsPbIBr2 device from 9.46% in Comparative Example 1 to 11.03% in Example 1, and overall increase the efficiency of the CsPbIBr2 perovskite solar cell by 16% ( Figure 6 ). At present, various interface modification methods and additive engineering have developed relatively maturely. It is believed that the application of further interface modification technology will surely make the photoelectric conversion efficiency of all-inorganic CsPbIBr2 devices leap forward.

Claims

1. A method for preparing CsPbIBr2 perovskite solar cells by precursor engineering, characterized in that: The following steps are involved: (1) Pretreatment of the substrate: ultrasonically clean the substrate using detergent, deionized water, acetone, and ethanol; after cleaning, blow dry, and treat with ultraviolet light; (2) Preparation of electron transport layer: depositing an electron transport material solution on a substrate by chemical bath deposition and sintering in a flat furnace to obtain an electron transport layer; (3) Preparation of precursor solution: The perovskite precursor solution uses three components: cesium bromide, lead iodide and lead bromide. The concentration c of the perovskite precursor solution is based on the cesium ion concentration, 1M<c≤1.4M; the molar ratio of cesium bromide: lead iodide: lead bromide is 2:1:1; the molar ratio of lead iodide: lead bromide = 1:1 is first dissolved in dimethyl sulfoxide, and stirred at 50-70°C overnight; cesium bromide is added in molar ratio, and stirred until completely dissolved to obtain a perovskite precursor solution; the hole transport layer precursor solution uses 2,2',7,7'- Tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene and a mixed additive are prepared in a ratio of 0.9-1g:1L, wherein the volume ratio of bis(trifluoromethane)sulfonyl imide:tris[4-tert-butyl-2-(1H-pyrazol-1-yl)pyridinium]cobalt tris(1,1,1-trifluoro-N-[(trifluoromethyl)sulfonyl]methanesulfonamide salt):4-tert-butylpyridine in the mixed additive is 1:(1.6-2):(1.5-1.9); (4) Preparation of perovskite film: preheat the substrate on a hot plate at 50-80°C, then spin-coat the perovskite precursor solution on the substrate, and anneal on a hot plate at 200-250°C for 5-15 minutes to obtain a perovskite film; (5) Preparation of hole transport layer: drop the hole transport layer precursor on the perovskite film and spin coat at 2000-3000 rpm for 30-50 seconds; (6) Preparation of electrodes: A layer of gold or silver is deposited on the hole transport layer by vacuum evaporation as an electrode.

2. The method for preparing CsPbIBr2 perovskite solar cells by precursor liquid engineering according to claim 1, characterized in that: The perovskite precursor solution and the hole transport layer precursor solution were filtered with a 0.22 μm filter head before use.

3. The method for preparing CsPbIBr2 perovskite solar cells by precursor liquid engineering according to claim 1, characterized in that: The spin coating process of the perovskite precursor solution uses 1000-2000 rpm for 10-20 seconds in the first stage and 3000-4000 rpm for 20-40 seconds in the second stage.

Citation Information

Patent Citations

  • Method for preparing high-performance all-inorganic perovskite solar cell based on copper bromide

    CN109728111A

  • Preparation method of high-efficiency cesium-lead-iodine-bromine inorganic perovskite thin film and solar cell based on high-efficiency cesium-lead-iodine-bromine inorganic perovskite thin film

    CN111048422A